Pengaruh Variasi Humektan pada Formulasi Hand Sanitizer serta Evaluasi Sediaan dan Daya Hambat terhadap Stapyhlococcus aureus - Qurrah A'yuniyyah Haryanto; Kurniawan Kurniawan; Solikah Ana Estikomah; Nurul Marfu'ah (University Of Darussalam Gontor, 2022)
The habits of the Indonesian people in carrying out hand hygiene activities are still very low with an average of only 12%. Along with the density of community activities, which consider hand washing a troublesome activity, it is also caused by the lack of clean water availability in the community. Therefore, there are hand sanitizer products that are practical without using water or commonly referred to as hand sanitizers. Hand sanitizer contains antiseptic substances that can kill germs on the palms due to the presence of alcohol (ethanol, propanol and isopropanol) and the phenol group (chlorhexidine and triclosan). Alcohol has the ability to inhibit bacterial growth, both against gram-positive and gram-negative bacteria, including MRSA (Methicilin Resistant of Staphylococcus aureus). The purpose of this study was to determine the effect of humectant variations on the evaluation of the preparation and the inhibition of Staphylococcus aureus bacteria. The results of the evaluation of the preparation of the hand sanitizer formulation are in accordance with the SNI No. 06-2588-1992, namely on the parameters of homogeneity, pH and dispersion. Meanwhile, the viscosity parameter is not in accordance with the standard. Variations in humectant concentration affect the evaluation of the preparation of the hand sanitizer gel formulation on the parameters of pH and dispersion. The formulation that had the greatest inhibition zone against Staphylococcus aureus was the formulation with the highest humectant concentration of propylene glycol, namely formulation 3 with an inhibitory power of 22.8 mm.